Theileria orientalis Ikeda infection does not negatively impact growth performance or breeding soundness exam results in young beef bulls at bull test stations - Guynn, Sierra R.; Greiner, Scott P.; Currin, John F.; Todd, S. Michelle; Assenga, Alphonce; Hungerford, Laura L.; Lahmers, Kevin K. (Frontiers in Veterinary Science, 2024)
Theileria orientalis Ikeda genotype is an emerging cattle disease in the US. Since 2017, when T. orientalis Ikeda was discovered in beef cattle in two counties in Virginia, cattle infections have risen to include ~67% of Virginia counties and 14 states. Consistent with New Zealand studies, many infected herds in Virginia were >90% positive upon initial testing without overt evidence of infection. Central bull tests present a unique opportunity to study the effects of T. orientalis Ikeda infections, as bulls from multiple source herds are consolidated, fed, and housed similarly to evaluate the bulls for growth performance and breeding soundness. The objective of this study was to determine if infection with T. orientalis Ikeda affected the average daily gain (ADG), yearling weight (AYW) and breeding soundness of bulls at two test stations in Virginia over a period of years. For T. orientalis Ikeda testing, DNA was extracted from whole blood for quantitative polymerase chain reactions. The number of bulls infected with T. orientalis Ikeda at initial delivery to the stations increased significantly over the years studied. Multivariable linear regression models, using Angus bulls from Virginia test stations, indicated no significant effect on ADG or AYW in bulls that became test positive during the test or were positive for the duration, compared to Angus bulls that were negative for the duration. At LOC A, the odds of passing a breeding soundness exam (BSE) were not significantly different for bulls that turned positive during the test or were positive for the duration, compared to bulls that were negative for the duration of the test. At LOC B, bulls that became positive during the test were 2.4 times more likely (95% CI: 1.165 -4.995, P = 0.016) to pass their BSE compared to bulls that remained negative throughout the test. We do not suppose that an obscured infection of T. orientalis Ikeda is protective for bulls to pass a BSE. However, this study demonstrates an obscured infection of T. orientalis Ikeda does not negatively affect weight gain or achievement of a satisfactory BSE rating at the central bull test stations in Virginia.